Somatic problems of HIV-Medicine: AIDS-related lymphomas - A. V. Pivnik; Y. G. Parhomenko; Y. A. Krivolapov; O. A. Tishkevich; V. G. Korovushkin; A. M. Kovrigina; M. B. Grusdev; L. D. Grinshpun; I. A. Berdisheva; N. V. Seregin; A. O. Tuaeva; E. B. Likunov; et al. (Онкогематология)
We followed 66 lymphoma -AIDS patients (pts): aggressive lymphomas were diagnosed in 48 pts (male — 35, female — 13, median age 32.5±1.2) and Hodgkin's lymphoma was established in 18 pts (male — 14, female — 4, median age 34.1±2.3). Median duration time from HIV exposure to the onset of lymphomas was 5 years (2—16 years). A part of pts was receiving HAART. 85 % of pts were drug users and association with HCV was shown in 60 % of them, with HCV and HBV- in 25 %. Sexual transmission was mentioned in 15 % of pts. «Immune status»: CD4 counts were from 50 to 500 (median 225) cells in mcL. Viral load was from 400 to 75000 (median 38000) copies in mcL. Histological diagnosis: diffuse large cell lymphomas — 60%, Burkitt lymphoma — 16%, follicular lymphoma — 12%, MALT-lymphomas-6%, T- cell lymphoma — 4%, primary CNS lymphoma — 2%. CHOP and CHOP-like courses had received 26 pts. Results: 3-year overall survival — 52%, 3-year disease free survival — 32%. Block therapy A-B-C of BFM — NHL— 90 and LB-M-04 with and without Mabthera had received 12 pts. Results: 3-year overall survival — 48%, 3-year disease free survival — 38%. After treatment CD4 count was 60 — 700 (median 316) cells in mcL, viral load 400 to 25000 (median 3000) copies in mcL. 75% of Hodgkin's lymphoma patients had III—IV stages of disease. Initial immune status: CD4 counts from 50 to 730 (median 363) cells in mcL, viral load — from 14000 to 150 000 (median 100 000) copies in mcL. Histological variants: mixed cellularity — 14 pts, lymphoid depletion — 3 pts, nodular sclerosis — 1 pt. Chemotherapy had received 11 pts: ABVD with or without radiotherapy — 8 pts, BEACOPP-escalated with or without radiotherapy — 3 pts. Complete 3-year remissions were achieved in 2 pts. Other pts are on therapy. After treatment CD4 counts were 184 — 900 (median 400) cells in mcL, viral load — 435000 (median 100 000) copies in mcL. Modern treatment approaches in lymphoma -AIDS pts can lead to complete remission, as well as in general non-HIV positive population.